The Impact of Perceived Exploitation on Health-related Outcomes - Costa, S.; Coyle-Shapiro, J. A-M.; Corlett, S.; Aguiar, T. R. (Academy of Management Proceedings, 2025)
Recent research argues that exploitative working relationships can be present in any context and experienced by any employee, but its prevalence is unknown. We expand the theory of the effects of employees’ perceptions of exploitation by proposing key processes (emotional, cognitive and motivation) and outcomes (job-related emotional exhaustion and somatic complaints). Specifically, we suggest that negative emotions, effort-reward imbalance and thwarted psychological needs are intertwined mechanisms linking perceived exploitation to health-related outcomes. In two experiments and a field study, we show that perceived exploitation predicts negative emotions, effort-reward imbalance and thwarted psychological needs. We further found that perceived exploitation has spillover effects on employees’ health. However, the effect is only significant for the cognitive and emotional path.